Penerapan Konsep Intervensi Harga Menurut Pemikiran Ekonomi Abu Yusuf dan Ibnu Taimiyah di Era Modern - Yulita Astri; Hendra SEI MA (JIKEM: Jurnal Ilmu Komputer, Ekonomi dan Manajemen, 2023)
Research was conducted to find out about how the comparison of economic thought believed by Abu Yusuf and also the thought of Ibn Taymiyah related to changes that occur in prices and also price intervention. The type of researcher is literature research. There are two types of data used in this study, namely primary and secondary data. The analytical method used in the research is descriptive qualitative. Meanwhile, the discussion is carried out using the deductive method. From the conclusions that can be drawn by researchers produce conclusions (i) the thoughts of Abu Yusuf and Ibn Taymiyah argue that fluctuations that occur in prices are caused by Allah SWT who has arranged it. (ii) the idea of price intervention itself is different from the two experts. Where Abu Yusuf did not agree about the intervention of prices while the Ibn Taymiyyah clan agreed that in the market itself there were price imperfections. (iii) the ideas of Abu Yusuf and Ibn Taymiyyah have differences and similarities